Etruria and Anatolia (Cambridge, United Kingdom ; New York, NY)
xxiii, 344 sayfa
Keywords: “This book offers the first comprehensive study of Etruscan and Anatolian cultures as agents of artistic exchange rather than as side characters in a Greek-focused narrative. Diverse chapters synthesize a wide range of material evidence, from tomb architecture and furniture to painted vases, terracotta reliefs, and magic amulets. By identifying shared practices, common visual language, and movements of objects and artisans (not only from east to west but also from west to east), this volume illuminates many varied threads of the interconnected ancient Mediterranean fabric. Rather than trying to account for similarities with one, overarching theory, it presents multiple, simultaneous modes and implications of connectivity while also recognizing the distinct local identities expressed even through shared artistic and cultural traditions.” --